KEPEMIMPINAN PENDIDIKAN PROFETIK NABI MUHAMMAD: TINJAUAN LITERATUR TENTANG MODEL INSPIRATIF DALAM MEMBANGUN GENERASI BERAKHLAK DAN BERILMU - Asyibli, Basri; Al Faqih, Saad; Heriansyah, M Arie Firdaus; Bachtiar, Machdum; Muslihah, Eneng (STKIP Pesisir Selatan, 2025)
This research is motivated by the importance of education as the key to the progress of the nation and the formation of character based on Islamic values. However, many Islamic educational institutions experience ups and downs in leadership quality that have an impact on the character of students, which is due to the lack of prophetic leadership examples in the style of the Prophet Muhammad ﷺ. The purpose of this research is to identify and analyze the prophetic leadership concept of the Prophet Muhammad ﷺ as well as his educational strategies in building a generation with noble character. The method used is literature review by reviewing various relevant journals, articles, and books in the last 10 years to obtain a strong theoretical foundation. The results of the study show that prophetic leadership based on four main values—siddiq (honest), amanah (trustworthy), fathonah (intelligent), and tabligh (communicative)—is an effective ideal leadership model in modern Islamic education. The educational strategy of the Prophet Muhammad ﷺ which integrates spiritual, moral, and scientific aspects has proven to be able to produce superior generations and trustworthy leaders. The implications of this study affirm the importance of applying prophetic values in education management to improve the quality of institutions and job satisfaction of educators.